Household Food Security, Child Dietary Diversity and Copping Strategies among Rural Households. The Case of Kole District in Northern Uganda - Elolu, Samuel; Agako, Allod; Okello, Daniel Micheal (ResearchGate, 2022)
Household food security, feeding practices, dietary diversity and copping strategies to household food insecurity are largely interconnected. Using a cross sectional study approach involving 162 mothers and care givers in Kole district of NorthernUganda, this study examined the scenarios of household food security status, child feeding practices, dietary diversity and copping strategies. The study revealed that majority of the households (55%) were food secure with an overall observation of low dietary diversity at the household level (72.8%), largely showing dominance of starch-based Cereals, roots and tubers (82%) and limited consumption of other food groups, notably fruits, vegetables, meats and dairy products (18% combined). In terms of feeding practices, majority of the children were fed breast milk for at least 24 months, with mandatory exclusive breastfeeding highly adhered to, but the introduction of complementary foods often delayed and not well planned. Results also showed that a wide range of coping strategies are employed however the major ones were, reliance on less preferred food (54.9%), limiting portions of meals (35.2%), reducing number of melas taken in a day (29%), and gathering wild fruits and harvesting immature crops (29.6%). Generally, it was observed that household food security is a strong determinant of dietary of child dietary diversity, may influence feeding practices and the range of coping strategies applicable to households when they experience food insecurity. It is apparent that nutritional education, household size and livelihood diversity also play a significant role in as far as household food security status, child feeding, diversity and food insecurity copping are concerned within rural households.
Keywords: Child dietary diversity, food security, feeding practices, livelihood, diversity